Structural Value Of Empyak - A. Robbi Maghzaya; Prihatmaji Yulianto; Pradipto Eugenius (Unika Soegijapranata Semarang, 2017)
ABSTRACT Empyak is a part of the traditional building that must be developed to preserve its existence. This paper explores the impact of construction method and structural behavior of empyak. The identification of how structurally work is essential as a primary information to develop the construction of empyak. Initially, a model with scale 1:3 was made to understand structural behavior under the seismic simulation. Some observation will be done to find out the changing of its shape under seismic forces. The results of this research are limited to understand the function of every element in the building stability. The result of the study will be useful for the development of traditional architecture. Empyak not only regards as a construction element but also as a structural element, which is the subject of the study. Keywords: Empyak, structure, construction, bamboo ABSTRAK Empyak adalah salah satu elemen bangunan tradisional Yogyakarta yang perlu dilestarikan. Artikel ini membahas mengenai konstruksi empyak terhadap perilaku struktur bangunan keseluruhannya. Bagaimana empyak bekerja sebagai elemen struktural perlu dipelajari untuk dikembangkan dengan metode yang lebih modern. Pemahaman mengenai perilaku struktur empyak dilakukan dengan pengamatan model konstruksi dibawak berbagai karakter pembebanan. Observasi terhadap model berfungsi untuk mengetahui perubahan bentuk setelah dilakukan pembebanan. Penelitian ini dibatasi pada fungsi-fungsi struktural setiap elemen empyak untuk mendapatkan bangunan yang stabil. Penelitian ini bermanfaat untuk memahami bagaimana nilai-nilai konstruksi dan struktur yang ada dalam konstruksi empyak. Keywords : Empyak, struktur, konstruksi, bambu